Temporomandibular joint dysfunction as a cause of facial pain- a case report - Devaraj, Navin Kumar (Journal of Rheumatology Publishing, 2019)
Temporomandibular joint dysfunction (TMJD) is one of the rare causes of facial pain. Its’ onset is often insidious. It can be a difficult condition to manage as most sufferers tend to have a chronic clinical course. This case report will look at a young man with TMJD and what options are available for its’ management.